Application of systematic monitoring and mapping techniques: Assessing land restoration potential in semi-arid lands of Kenya - Winowiecki, Leigh Ann; Vågen, Tor-Gunnar; Kinnaird, Margaret F.; O'Brien, Timothy G. (Geoderma, 2018)
[Display omitted] •Prediction models for soil properties using MIR spectroscopy performed well.•Woody and herbaceous cover influenced topsoil OC more than vegetation class.•Erosion had a strong effect on SOC across each vegetation class.•Predictive maps of SOC and erosion were generated using Landsat 8 reflectance.•Restoration potential was assessed using key land and soil health variables.